Pengaruh Financial Technology dan Struktur Modal Terhadap Profitabilitas Pada Sektor Perbankan di Bursa Efek Indonesia Periode 2020-2023 - Nevita Feinbrianti (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the influence of financial technology and capital structure on profitability in the banking sector by using secondary data, namely financial statements listed on the Indonesia Stock Exchange for the 2020-2023 period. This study uses purposive sampling techniques. The data were tested using multiple linear regression analysis, classical assumption test, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study show that the t-test of the financial technology variable (X1) has a t-value of > ttable (2.344 > 1.65356) and a significant level (0.020 < 0.05), this means that the financial technology (fintech) variable has a significant effect on profitability. The t-test of the Capital Structure variable (X2)t-value calculated > ttable (1.928 > 1.65356) with a significant level (0.055 > 0.05) means that the Capital Structure variable has no effect and is not significant on Profitability. As for the F test, it is known that the ftable > calculation (3.833 > 2.66) with a significant level (0.023 < 0.05), meaning that the independent variables, namely financial technology (X1) and Capital Structure (X2), have a joint effect on the bound variable, namely Profitability (Y). Meanwhile, the correlation analysis (r) of 0.596 shows a fairly strong correlation between financial technology (X1) and Capital Structure (X2) to profitability (Y) in the banking sector listed on the Indonesia Stock Exchange for the 2020-2023 period. Meanwhile, the analysis of the determination coefficient (R2) obtained R2 = 0.345 (34.5%). This reveals that the influence of financial technology (X1) and Capital Structure (X2) has an effect on Profitability (Y) by 34.5%. While the remaining 65.5% was influenced by other variables that were not included in this study.